IMPLEMENTATION OF HIGH SCHOOL TEACHER COMPETENCY DEVELOPMENT (MULTI-SITE STUDY AT SMAN 1 KUALA KAPUAS AND SMAN 1 BASARANG) - Dewi Yuliana; Ahmad Suriansyah; Ngadimun Ngadimun (LP2M IAI Al-Khairat Pamekasan, 2026)
This research aims to determine the implementation of the Development School Teacher Competence Senior High School at SMAN 1 Kuala Kapuas and SMAN 1 Basarang. Study This use method study, qualitative with a phenomenology type study. Data sources used is interview with informants and retrieval the criteria based on technique snowball sampling. Data collection techniques used is interviews, documentation and field observations. After the data is collected, then done analysis use data analysis in One social situation according to Miles & Huberman and cross- site data analysis flow model. Validity techniques the data use degrees credibility, transferability, dependability, confirmability and triangulation. Research results show that First about readiness development teacher competency at both research sites. This show existence role managerial head school in determine policy development and teacher competence in schools. While in the planning process development teacher competency at both research sites has designed in a way analytical and systematic in accordance with the personal needs of teachers and schools. Secondly, in the implementation development teacher competency at both research sites show existence emphasis on utilizing technology and information in training development teacher competency in schools. The activities implementation development in a technical way, covering coaching, giving assignments, education or studies further, career development, conferences, workshops, in-house training and seminars. The third about facilities and infrastructure school in facilitate development teacher competence at both sites. The infrastructure at the school is very adequate and has proper function like room training, laboratories, and technology up-to-date information and convenient access to the power source.